2020
DOI: 10.3390/cancers12092340
|View full text |Cite
|
Sign up to set email alerts
|

A Biobank of Colorectal Cancer Patient-Derived Xenografts

Abstract: Colorectal cancer (CRC) is a challenging disease, with a high mortality rate and limited effective treatment options, particularly for late-stage disease. Patient-derived xenografts (PDXs) have emerged as an informative, renewable experimental resource to model CRC architecture and biology. Here, we describe the generation of a biobank of CRC PDXs from stage I to stage IV patients. We demonstrate that PDXs within our biobank recapitulate the histopathological and mutation features of the original patient tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 90 publications
3
10
0
Order By: Relevance
“…Hence, a longer latency time may increase the engraftment rate. In line with our findings, a recent study by Abdirahman et al also reported an allowed six month latency period until established CRC PDX growth [ 19 ], and Chijiwa et al stated that animals were sacrificed as “failed” if mice did not develop PDX growth over six months from engraftment [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, a longer latency time may increase the engraftment rate. In line with our findings, a recent study by Abdirahman et al also reported an allowed six month latency period until established CRC PDX growth [ 19 ], and Chijiwa et al stated that animals were sacrificed as “failed” if mice did not develop PDX growth over six months from engraftment [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…PDXs preserve the biological characteristics of tumors better than CDX models, and therefore serve as a better research model for personalized cancer treatment. PDXs with established growth may be considered first generation xenografts, while several studies have made PDX lines (third generation PDX) stored in a PDX line biobank for future studies [ 19 ]. By using first generation xenografts there is a risk of failure to establish growth, while growth has already been confirmed with second or third generation PDX lines.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the HROC PDX models precisely recapitulated the mutation profiles of the original patient tumors, thereby confirming previous data [32,38,39]. In particular, our study pointed out that pathogenic or likely pathogenic mutations detected in the original tumors were maintained in the PDX tumors.…”
Section: Discussionsupporting
confidence: 88%
“…Comparative pathomorphological analysis and genetic identity testing confirmed the close proximity of the HROC-Xenobank models to the original patient tumors. Moreover, we could confirm previous findings that PDX models, in the majority of cases, maintain the original tumor’s biological features [ 2 , 3 , 32 ]. For each individual HROC PDX model we described in detail, the pathomorphological structures were reproduced from the original patient tumor.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation